Integrating Fish Assemblage Data, Modeled Stream Temperatures, and Thermal Tolerance Metrics to Develop Thermal Guilds for Water Temperature Regulation: Wyoming Case Study. Issue 4 (20th May 2019) - Mandeville, Caitlin P.; Rahel, Frank J.; Patterson, Lindsay S.; Walters, Annika W.
Abstract: Many streams are experiencing increased average temperatures due to anthropogenic activity and climate change. As a result, surface water temperature regulation is critical for preserving a diverse stream fish species assemblage. The development of temperature regulations has generally been based on laboratory measurements of individual species' thermal tolerances rather than community response to temperature in the field, despite multiple limitations of using laboratory data for this purpose. Using field data to develop temperature regulations may avoid some of the limitations of laboratory data, but the use of field data comes with additional challenges that prevent its widespread adoption. We used Wyoming stream fish assemblages as a case study to examine the feasibility of addressing the limitations of field and laboratory data through a hybrid approach that integrates both types of data to classify species into thermal guilds that can potentially inform regulatory standards. We identified coldwater, coolwater, and warmwater classes of sites with modeled mean August temperatures of <15.5, 15.5–19.9, and >19.9°C, respectively. We used species' associations with these temperature classes to place species into site‐groups. Finally, we used standardized laboratory measures of species' upper acute and chronic thermal tolerances to identify and reclassify species with unusual thermal distributions. Through this process we classified species into five thermal guilds that may be useful for surface water temperature regulation in Wyoming. Our approach addresses the limitations identified for field and laboratory data and demonstrates a framework that could be used for incorporating multiple types of data to develop temperature standards.